2018
DOI: 10.1200/jco.2018.78.3977
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Breast Cancer in Nigerian Women

Abstract: PurposeAmong Nigerian women, breast cancer is diagnosed at later stages, is more frequently triple-negative disease, and is far more frequently fatal than in Europe or the United States. We evaluated the contribution of an inherited predisposition to breast cancer in this population.Patients and MethodsCases were 1,136 women with invasive breast cancer (mean age at diagnosis, 47.5 ± 11.5 years) ascertained in Ibadan, Nigeria. Patients were selected regardless of age at diagnosis, family history, or prior genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 31 publications
10
93
1
Order By: Relevance
“…and BRCA2 mutations in a cohort of Nigerian patients with breast cancer, and mutation rates as high as 25% are reported in patients with breast and ovarian cancer in India. 7,8 These rates are comparable to the BRCA1 and BRCA2 mutation rates initially characterized in patients of Ashkenazi ancestry with breast cancer. Large biobanking studies of unselected general populations are also finding higher frequencies of BRCA1 and BRCA2 mutations than expected.…”
supporting
confidence: 63%
“…and BRCA2 mutations in a cohort of Nigerian patients with breast cancer, and mutation rates as high as 25% are reported in patients with breast and ovarian cancer in India. 7,8 These rates are comparable to the BRCA1 and BRCA2 mutation rates initially characterized in patients of Ashkenazi ancestry with breast cancer. Large biobanking studies of unselected general populations are also finding higher frequencies of BRCA1 and BRCA2 mutations than expected.…”
supporting
confidence: 63%
“…Note that only 11 published studies were found that included male BRCA1/2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty‐eight studies were included in the present report: 16 studies of Sub‐Saharan Africans (Awadelkarim et al, ; Biunno et al, ; Diez et al, ; Elimam et al, ; Fackenthal et al, ; Fackenthal et al, ; Francies et al, ; Gao et al, ; Luyeye Mvila et al, ; Stoppa‐Lyonnet et al, ; van der Merwe et al, ; Zhang et al, ; Zhang et al, ; Zhang, Fackenthal, Huo, Zheng, & Olopade, ; Zheng et al, ; Zoure et al, ), 27 of African Americas (Arena et al, ; Arena et al, ; Arena et al, ; Castilla et al, ; Churpek et al, ; Dangel et al, ; Futreal et al, ; Ganguly, Dhulipala, Godmilow, & Ganguly, ; Q. Gao, Neuhausen, Cummings, Luce, & Olopade, ; Q. Gao, Sveen, Cummings, & Olopde, ; Q. Gao et al, ; Gayol et al, ; Haffty et al, ; Hall et al, ; John et al, ; Kanaan et al, ; Kedar‐Barnes et al, ; Lynce et al, ; Martin et al, ; Miki et al, ; Nanda et al, ; Olopade et al, ; Pal et al, ; Pal et al, ; Pal, Permuth‐Wey, Holtje, & Sutphen, ; Panguluri et al, ; Shen et al, ; Sutphen & Ferlita, ; Whitfield‐Broome, Dunston, & Brody, ), and three of Afro‐Caribbean populations (Akbari et al, ; Donenberg et al, ; Donenberg et al, ) and one study reporting SRAA of unspecified geography (Hall et al, ). From these papers, we identified 414 BRCA1 and 187 BRCA2 PSVs, and 108 unique BRCA1 and 103 unique BRCA2 PSVs.…”
Section: Resultsmentioning
confidence: 99%
“…Note that only 11 published studies were found that included male BRCA1/ 2 PSV carriers, but no additional BRCA1/2 PSVs were identified from these reports. Forty-eight studies were included in the present report: 16 studies of Sub-Saharan Africans (Awadelkarim et al, 2007;Biunno et al, 2014;Diez et al, 2011;Elimam et al, 2017;Fackenthal et al, 2005;Fackenthal et al, 2012;Francies et al, 2015;Gao et al, 2000;Luyeye Mvila et al, 2014;Stoppa-Lyonnet et al, 1997;van der Merwe et al, 2012;Zhang et al, 2009;Zhang et al, 2012;Zhang, Fackenthal, Huo, Zheng, & Olopade, 2010;Zheng et al, 2018;Zoure et al, 2018), 27 of African Americas (Arena et al, 1996);Arena et al, 1997;Arena et al, 1998;Castilla et al, 1994;Churpek et al, 2015;Dangel et al, 1999;Futreal et al, 1994;Ganguly, Dhulipala, Godmilow, & Ganguly, 1998;Q. Gao, Neuhausen, Cummings, Luce, & Olopade, 1997;Q.…”
Section: African Ancestry Individuals With Brca1/2 Pathogenic Sequementioning
confidence: 99%
“…Using state‐of‐the‐art genomic technologies for their analysis, the study’s multinational team published its findings from more than 20 years of research in the August 21, 2018, issue of Journal of Clinical Oncology . Of the 1136 women with invasive breast cancer who were enrolled in the study, the disease among Nigerian women who had mutations in their breast cancer genes was far more advanced than in women in the United States with the same genetic mutations, the authors note.…”
Section: Investigating Breast Cancer In Nigeriamentioning
confidence: 99%